ANALISIS PENGARUH LDR, CAR, ROA, DAN FAKTOR EKSTERNAL PERBANKAN TERHADAP VOLUME KPR PADA BANK PERSERO PERIODE 2008-2012 - Pradana, Yoga; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2013)
Mortgage loans is one of the credit portfolio of banks that are experiencing increased lately. Improved constantly in channeling housing loan is feared will cause a variety of problems like the bubble property and nonperforming loans. This research purpose to examine influence of Loan to Deposite Ratio (LDR), Capital Adequacy Ratio (CAR), Return on Asset (ROA), BI Rate, and Inflation to Mortgage Loan distribution on the State Banks in Indonesia. The population that was used in this research is all the State Bank in Indonesia. While the sample is LDR, CAR, ROA, BI Rate and inflation data on the State Bank during 60 months (year observations from 2008 to 2012). Sample taking technic used purposive sampling and analysis method that was used is multiple linear regression.Based on the results of testing using multiple linear regression analysis, it can be noted that the volume of mortgage loans influenced by internal and external variable banking. It can be seen from the results of the partial test (t-test), determination of coefficients test, and the simultaneous significance tests (f-test). Based on the partial tests can noted that all independent variables namely LDR, CAR, ROA, the BI rate, and inflation has a positive and significant impact on the volume of mortgage loans. Based on the simultaneous significance tests together all the variables entered into the models of research have a significant influence on the dependent variable. While based on the determination of coefficients test, be aware that the independent variables the dependent variable can predict very well.